Altered hydroxylation of estrogen in patients with postmenopausal osteopenia - Lim, SK; Won, YJ; Lee, JH; Kwon, SH; Lee, EJ; Kim, KR; Lee, HC; Huh, KB; Chung, BC (ENDOCRINE SOC, 1997)
To study the possible contributions of the differences in estrogen metabolism to bone mass in postmenopausal osteopenia, spinal and femoral bone mineral densities (BMD) were measured, and 18 urinary metabolites of estrogen were analyzed by a gas chromatography-mass spectrometry assay system in 59 postmenopausal women (5-10 yr after menopause). The BMD of the spine and femoral neck showed positive correlations with body weight, height, and body mass index as we expected. Compared to nonosteopenic subjects, there were no significant differences in serum estrone (E(1)) and estradiol (E(2)) levels in patients with osteopenia. However, the urinary 16 alpha-hydroxyestrone [16 alpha-(OH)E(1)] level was significantly lower in patients with spinal osteopenia (P < 0.001). Among the 18 urinary metabolites of estrogen, the 16 alpha-(OH)E(1) and 16 alpha-(OH)E(1)/2-hydroxyestrone [2-(OH)E(1)) ratio showed positive correlations with spinal BMD (P < 0.05), whereas 2-(OH)E(2) showed a negative correlation with femoral neck BMD (P < 0.05). The urinary 16 alpha-(OH)E(1) level also revealed a positive correlation with the age-matched z score of BMD in the spine (P < 0.05). In multiple stepwise regression analysis, weight, 16 alpha-((OH)E(1), interaction between 16 alpha-(OH)E(1) and 2-(OH)E(2), 2-(OH)E(2), and years after menopause were statistically significant for spinal BMD (r(2) = 0.4968). For femoral neck BMD and weight, 16 alpha(-(OH)E(1) and 2-(OH)E(2) were the independent determinants (r(2) = 0.3369). In conclusion, the activity of estrogen 16 alpha-hydroxylase was decreased and/or the activity of estrogen 2-hydroxylase was enhanced in post menopausal osteopenia. We speculated that these derangements may serve as contributing factors for the acceleration of bone loss in postmenopausal osteoporosis.
Keywords: BONE LOSS; HORMONE LEVELS; WOMEN; BREAST; CANCER; OVARIAN; AGE